2018
DOI: 10.1021/acs.langmuir.8b01073
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid–Block Copolymer Hybrid Vesicles with Lysosomal Escape Ability

Abstract: The success of nanoparticulate formulations in drug delivery depends on various aspects including their toxicity, internalization, and intracellular location. Vesicular assemblies consisting of phospholipids and amphiphilic block copolymers are an emerging platform, which combines the benefits from liposomes and polymersomes while overcoming their challenges. We report the synthesis of poly(cholesteryl methacrylate)- block-poly(2-(dimethylamino) ethyl methacrylate) (pCMA- b-pDMAEMA) block copolymers and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…93 Compared to liposomes they also showed an enhanced lysosomal escape. 95 Instead of using lipid-polymer conjugates, both types of macromolecules eventually also form hybrid vesicles if they are just blended. The successful formation of such hybrid assemblies that bring together the biocompatibility and softness of liposomes and robustness and chemical versatility of polymersomes depends on the correct choice of the amphiphilic building blocks.…”
Section: Biohybrid Polymersomes With Membrane Functionalisationmentioning
confidence: 99%
“…93 Compared to liposomes they also showed an enhanced lysosomal escape. 95 Instead of using lipid-polymer conjugates, both types of macromolecules eventually also form hybrid vesicles if they are just blended. The successful formation of such hybrid assemblies that bring together the biocompatibility and softness of liposomes and robustness and chemical versatility of polymersomes depends on the correct choice of the amphiphilic building blocks.…”
Section: Biohybrid Polymersomes With Membrane Functionalisationmentioning
confidence: 99%
“…Synthetic cells that can sense and respond to physical stimuli, sense and recognize chemical signals have been achieved. [364][365][366] Currently, to respond to biochemical signal by synthesizing molecules from surroundings and secreting remains challenging.…”
Section: Cell-environment and Cell-cell Communications: Adhesion Senmentioning
confidence: 99%
“…These hybrid vesicles have higher permeability to small dyes like carboxyfluorescein or calcein with respect to polymersomes [11][12][13] and it has been recently shown that the hybrid vesicles permeability could be increased by adding phospholipase A2 that can selectively degrade lipids [14]. Examples of hybrid nanoscale polymersomes have been proposed for applications in nanomedicine and seemed to improve the targeting efficiency [15,16]. Interestingly, hybrid vesicles at the micron scale are valid alternatives to giant liposomes as simplified cell models for a deeper understanding of fundamental biological processes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Zong et al [16] to confirm the presence of both phospholipids and the block copolymer in the same membrane, pCMA constitutes the hydrophobic block, while the pH-sensitive pDMAEMA constitutes the hydrophilic block. These GUVs were electroformed and the maximum polymer content was 70% w/w (corresponding to 3.6 mol % using Mn=47.5 kD as reported in Table of the cited work).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation